Literatur Review: Pengaruh Senam Kaki Diabetes Terhadap Kontrol Gula Darah Pada Pasien Diabetes Melitus - Fiqriyah, Indhira Kurniastining; Rosyid, Fahrun Nur (Universitas Malahayati, 2024)
ABSTRACT Diabetes mellitus is a disease with a high mortality rate with its prevalence increasing with increasing age. Therefore, action or intervention is needed that can be useful for controlling blood sugar for diabetes mellitus sufferers, where foot exercises are one of the non-pharmacological therapies that have the effect of controlling blood sugar for diabetes mellitus sufferers. The aim of this research is to determine whether foot exercises are effective in controlling blood sugar in people with diabetes mellitus. Using electronic databases from national and international publications such as Google Scholar and PubMed, and literature reviews are the research methodologies used. Key words from Google Scholar are foot exercises, high blood sugar, cardiovascular disease, healing, care, treatment and rehabilitation, and from PubMed the keywords Foot Exercises or High Blood Sugar or Cardiovascular Disease or Healing Care or Treatment or Rehabilitation. After conducting a preliminary literature search on Google Scholar and PubMed, 350 articles with the same title were found, 267 of which were discarded because they were less relevant to the issue of foot exercises to control blood sugar in diabetes mellitus patients. Requirements were met by 12 full-text articles. In conclusion: diabetes mellitus patients can control blood sugar effectively by using foot exercises. This approach can be used as an intervention or alternative for non-pharmacological blood sugar measures because it can drastically control blood sugar after exercise. Keyword: Diabetes Mellitus, Blood Sugar, Foot Exercises ABSTRAK Diabetes mellitus merupakan salah satu penyakit dengan angka kematian yang tinggi dengan peningkatan prevalensinya diiringi oleh bertambahnya usia. Maka dari itu diperlukan tindakan atau intervensi yang dapat bermanfaat untuk mengontrol gula darah bagi penderita diabetes mellitus yang mana senam kaki merupakan salah satu terapi non farmakologis yang berpengaruh mengontrol gula darah bagi penderita diabetes mellitus. Tujuan penelitian ini adalah untuk memastikan apakan senam kaki efektif mengontrol gula darah pada penderita diabetes mellitus. Menggunakan database elektronik dari publikasi nasional dan internasional seperti Google Scholar dan PubMed, dan tinjauan literatur adalah metodologi penelitian yang digunakan. Kata kunci dari Google Scholar adalah Senam kaki, gula darah tinggi, penyakit kardiovaskular, penyembuuhan, perawatan, pengobatan, dan rehabilitasi, dan dari PubMed dengan kata kunci Foot Exercises or High Blood Sugar or Cardiovascular Disease or Healing Care or Treatment or Rehabilitation. Setelah dilakukan penelusuran literatur pendahuluan di Google Scholar dan PubMed, ditemukan 350 artikel dengan judul yang sama, 267 di antaranya dibuang karena kurang relevan dengan isu senam kaki untuk mengontrol gula darah pada pasien diabetes mellitus. Persyaratan dipenuhi oleh 12 artikel teks lengkap. Kesimpulannya: pasien diabetes mellitus dapat mengontrol gula darah secara efektif dengan menggunakan senam kaki. Pendekatan ini dapat dimanfaatkan sebagai intervensi atau alternatif tindakan gula darah non-farmakologis karena dapat mengontrol gula darah secara drastis setelah senam. Kata Kunci: Diabetes Mellitus, Gula Darah, Senam Kaki.